Transition to turbulence in a turbomachinery environment - Read, Simon (Cranfield University, 1997)
This thesis aims to contribute to the understanding of transitional flows in the blade boundary layers of axial compressors. Two experiments are described, the first examining in detail the transitional boundary layer on a simulated controlled-diffusion blade and the second surveying the mid-height flowfield in an embedded stage of a low-speed axial compressor. The velocity distribution on the simulated blade is identical to the Velocity distribution on the suction surface of the blades in the axial compressor. At 2 Reynolds numbers and 3 levels of freestream turbulence, a single hot wire was used to conduct a boundary layer survey on a simulated controlled-diffusion blade. Integral parameters of the boundary layers are explored to dene the length and nature of transition. At low Reynolds number there is a separated or near separated region at the leading edge which does not lead to turbulence. Transition covers a length of approximately 20% of the blade chord, starting between 20% and 30% chord. The position of transition is strongly influenced by the level of freestream turbulence. Most of the transition process occurs within the decelerating flow region which exists from 20% of the chord. At high Reynolds number, a leading edge separation bubble leads to transition within 2% of the blade chord. Abu-Ghannam & Shaws correlation for the start and length of transition was found to predict the start of transition well for attached flows, but could not be relied upon for separated flows. It is apparent that the correlation was not designed for the very strong Velocity gradients in the leading edge region, and probably not for separated flow. _ Three flow conditions in the axial compressor were used: design speed, peak efficiency, low Reynolds number at peak efficiency (the machine was slowed to one-quarter speed) and design speed near the stall. Using hot wires at mid-height, axial and circumferential velocity and turbulence information was obtained. Wakes and structure within wakes are visible in the turbulence and Reynolds stress distributions. The wakes of more than one upstream blade row are visible; the region where two wakes intersect gives some information about interaction between a stator blade Wake and a rotor blade boundary layer. Some information is available about the length scale 'distribution inside and outside wakes. Secondary flow in the axial-circumferential plane shows motion within wakes and a vortex in the near-stall flowfield, shed preferentially at one point in the blade-passing cycle.